Experiencing music therapy with clients who have been affected by addiction within their families - Puskunigyte, Emilija (2020)
Research concerning music therapy in the field of addiction treatment is continuously growing. However, such work focuses mostly on the effectiveness of music therapy in helping the addict to recover, rarely investigating how music therapy is experienced and how it benefits the family members that carry a certain amount of the burden of their relative’s addiction. The current case study was conducted as an action research project with the purpose of experiencing group music therapy with the intended clients, following the action research cycle method of planning-action-reflection. Three participants were recruited for a group music therapy process of 10 one-hour-long sessions with a student music therapist. A narrative description of one cycle (Session IV) is provided along with other findings revealing meaningful changes in group development and group cohesiveness. Music therapy interventions such as clinical improvisation and song discussions (song sharing) are discussed as means of creating a safe and supportive environment for the clients.